The Indolinone MAZ51 Induces Cell Rounding and G2/M Cell Cycle Arrest in Glioma Cells without the Inhibition of VEGFR-3 Phosphorylation: Involvement of the RhoA and Akt/GSK3β Signaling Pathways - Park, Joo-Hee; Shin, Yoo-Jin; Riew, Tae-Ryong; Lee, Mun-Yong (PLOS ONE, 2014)
MAZ51 is an indolinone-based molecule originally synthesized as a selective inhibitor of vascular endothelial growth factor receptor (VEGFR)-3 tyrosine kinase. This study shows that exposure of two glioma cell lines, rat C6 and human U251MG, to MAZ51 caused dramatic shape changes, including the retraction of cellular protrusions and cell rounding. These changes were caused by the clustering and aggregation of actin filaments and microtubules. MAZ51 also induced G2/M phase cell cycle arrest. This led to an inhibition of cellular proliferation, without triggering significant cell death. These alterations induced by MAZ51 occurred with similar dose- and time-dependent patterns. Treatment of glioma cells with MAZ51 resulted in increased levels of phosphorylated GSK3β through the activation of Akt, as well as increased levels of active RhoA. Interestingly, MAZ51 did not affect the morphology and cell cycle patterns of rat primary cortical astrocytes, suggesting it selectively targeted transformed cells. Immunoprecipitation–western blot analyses indicated that MAZ51 did not decrease, but rather increased, tyrosine phosphorylation of VEGFR-3. To confirm this unanticipated result, several additional experiments were conducted. Enhancing VEGFR-3 phosphorylation by treatment of glioma cells with VEGF-C affected neither cytoskeleton arrangements nor cell cycle patterns. In addition, the knockdown of VEGFR-3 in glioma cells did not cause morphological or cytoskeletal alterations. Furthermore, treatment of VEGFR-3-silenced cells with MAZ51 caused the same alterations of cell shape and cytoskeletal arrangements as that observed in control cells. These data indicate that MAZ51 causes cytoskeletal alterations and G2/M cell cycle arrest in glioma cells. These effects are mediated through phosphorylation of Akt/GSK3β and activation of RhoA. The anti-proliferative activity of MAZ51 does not require the inhibition of VEGFR-3 phosphorylation, suggesting that it is a potential candidate for further clinical investigation for treatment of gliomas, although the precise mechanism(s) underlying its effects remain to be determined.